2018
DOI: 10.18632/aging.101359
|View full text |Cite
|
Sign up to set email alerts
|

NKILA inhibits NF-κB signaling and suppresses tumor metastasis

Abstract: The long non-coding RNA (lncRNA) NKILA (nuclear transcription factor NF-κB interacting lncRNA) functions as a suppressor in human breast cancer and tongue cancer. However, the clinical significance and biological roles of NKILA in esophageal squamous cell carcinoma (ESCC) remain unknown. In this study, we showed that NKILA was downregulated in ESCC tissues and cancer cells compared with their normal counterparts. Low NKILA expression correlated with large tumor size and advanced TNM stage, and predicted poor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 37 publications
4
46
0
Order By: Relevance
“…15,16 Moreover, Yang et al 18 demonstrated that knockdown of NKILA expression promoted cell viability and migration, and reversed cell apoptosis F I G U R E 4 The molecular mechanism of NKILA in rectal cancer cell. We found NKILA overexpression dramatically repressed rectal cancer cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Moreover, Yang et al 18 demonstrated that knockdown of NKILA expression promoted cell viability and migration, and reversed cell apoptosis F I G U R E 4 The molecular mechanism of NKILA in rectal cancer cell. We found NKILA overexpression dramatically repressed rectal cancer cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Moreover, Yang et al 18 demonstrated that knockdown of NKILA expression promoted cell viability and migration, and reversed cell apoptosis F I G U R E 4 The molecular mechanism of NKILA in rectal cancer cell. [14][15][16][17][18][19][20] In addition, NKILA was found to enhance the the anticancer effects of baicalein in hepatocellular carcinoma through modulating NF-κB signaling. B, NKILA overexpression inhibits p65 nuclear translocation and induces p65 cytoplasmic retention and the cytotoxicity of X-ray radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long non‐coding RNAs, a subset of non‐coding transcripts with more than 200 nucleotides in length, have been shown to play important roles in numerous biological processes, for example inflammation, immunity and various cancers . With the development of high throughput RNA sequencing approach, a variety of novel lncRNAs were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs, a subset of non-coding transcripts with more than 200 nucleotides in length, have been shown to play important roles in numerous biological processes, for example inflammation, immunity and various cancers. [22][23][24][25] With the development of high throughput RNA sequencing approach, a variety of novel lncRNAs were identified. However, due to the tissue specific and low expression properties, functional involvement of a majority of lncRNAs remains unclear, up to date.…”
mentioning
confidence: 99%